1988
DOI: 10.1113/expphysiol.1988.sp003170
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physostigmine Sulphate Eyedrops on Human Visual Function

Abstract: SUMMARYInstillation of 0 25 % physostigmine sulphate eyedrops in twelve subjects caused a sustained miosis, a transient reduction in near-point and a transient increase in the amplitude of accommodation. The latter had a peak at 30 min and had recovered by 90 min, though its amplitude varied widely between subjects. Contrast sensitivity to stationary grating patterns of 3-30 cycles/deg and phase-reversed grating patterns of 0-5-3 cycles/deg was reduced transiently with a time course similar to that of the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Previously, we showed that ocular instillation of physostigmine sulphate transiently reduced contrast sensitivity, with the nadir at 30 min and recovery by 90 min (Kay & Morrison, 1988). The deficit was contributed to both by the defocus resulting from the transient increase in accommodation and by a direct effect on the visual system.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Previously, we showed that ocular instillation of physostigmine sulphate transiently reduced contrast sensitivity, with the nadir at 30 min and recovery by 90 min (Kay & Morrison, 1988). The deficit was contributed to both by the defocus resulting from the transient increase in accommodation and by a direct effect on the visual system.…”
Section: Introductionmentioning
confidence: 84%
“…This improvement was attributed entirely to the increased depth of focus resulting from a miosis of 1 mm. So it is by no means clear whether organophosphorus anticholinesterases do effect spasm of accommodation in the way that physostigmine does (Kay & Morrison, 1988). If not, then this is a most remarkable difference for organophosphorus anticholinesterases which are noted for their great potency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most probable explanation is an effect of hyoscine directly on the retina, which is supported by its relatively rapid action on the iris and ciliary body (see Figure Z(a) and ( b ) ) . A precedent is the deleterious effect of physostigmine eyedrops on critical fusion frequency (Alpern and Jampel, 1959) and on contrast sensitivity to laser interference fringes (Kay and Morrison, 1988). The most probable route of absorption is transcorneal though systemic absorption from the nasal mucosa after drainage through the nasolacrimal canal may also arise (Shell, 1982).…”
Section: Contrast Sensitivitymentioning
confidence: 99%